2017
DOI: 10.1016/j.mam.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of vascular injury: Specialized lipid mediators and their evolving therapeutic implications

Abstract: Acute vascular injury occurs in a number of important clinical contexts, including spontaneous disease-related events (e.g. plaque rupture, thrombosis) and therapeutic interventions such as angioplasty, stenting, or bypass surgery. Endothelial cell (EC) disruption exposes the underlying matrix, leading to a rapid deposition of platelets, coagulation proteins, and leukocytes. A thrombo-inflammatory response ensues characterized by leukocyte recruitment, vascular smooth muscle cell (VSMC) activation, and the ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 111 publications
(187 reference statements)
1
44
0
Order By: Relevance
“…Moreover, the ω-3 modulatory action on l -type calcium channels may result in reduced cytosolic free Ca 2+ and Ca 2+ influx rate, which is believed to prevent the cytosolic calcium overload taking place during the ischemic insult [ 36 ]. The anti-inflammatory and anti-thrombotic effects of ω-3 PUFA have mainly been related to their metabolic conversion to oxygenated derivatives, which are broadly named oxylipins, and are highly bioactive factors acting at very low concentrations [ 37 , 38 ]. Following a stimulus, both the LC-ω-3 PUFA EPA and DHA or the ω-6 PUFA arachidonic acid (AA), are released from cell membranes and converted to oxylipins with similar structures, but often contrasting effects.…”
Section: ω-3 Pufa and Cardiovascular (Cv) Diseasesmentioning
confidence: 99%
“…Moreover, the ω-3 modulatory action on l -type calcium channels may result in reduced cytosolic free Ca 2+ and Ca 2+ influx rate, which is believed to prevent the cytosolic calcium overload taking place during the ischemic insult [ 36 ]. The anti-inflammatory and anti-thrombotic effects of ω-3 PUFA have mainly been related to their metabolic conversion to oxygenated derivatives, which are broadly named oxylipins, and are highly bioactive factors acting at very low concentrations [ 37 , 38 ]. Following a stimulus, both the LC-ω-3 PUFA EPA and DHA or the ω-6 PUFA arachidonic acid (AA), are released from cell membranes and converted to oxylipins with similar structures, but often contrasting effects.…”
Section: ω-3 Pufa and Cardiovascular (Cv) Diseasesmentioning
confidence: 99%
“…Recent investigations suggest that the evolving pharmacobiology of resolution may offer new candidate vascular therapeutics. 34 SPMs are naturally occurring autacoids and exert homeostatic effects across a range of disease models with biologic activity in picomolar to nanomolar concentrations. 10 In this study, we found that RvD1 delivered to the external surface of rabbit vein grafts at the time of implantation through either a Pluronic gel or a PLGA film reduced neointimal hyperplasia at 28 days by 50% to 61% compared with bypass-only controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has described biosynthetic pathways of SPMs in vascular tissues, signaling mechanisms, and vascular cell-specific responses to various SPMs. 34,38,41 Definition of a “resolution index” biomarker after acute vascular injury, similar to that employed in other models of sterile inflammation (eg, peritonitis), could also be useful as a surrogate end point for translational studies. 13,42,43 Along these lines, we observed an increase in the ratio of RvD1 to the proinflammatory lipid mediator LTB 4 in vein grafts treated with RvD1-loaded films.…”
Section: Discussionmentioning
confidence: 99%
“…After vascular injury, a variety of growth factors, cytokines and chemokines are synthesized and secreted, which can stimulate VSMCs phenotype switching, accelerate VSMCs migration to inner membranes, induce the excessive proliferation of VSMCs and further lead to vascular restenosis [34][35][36]. PDGF, mainly expressed in VSMCs and endothelial cells, promote mitosis and play an important role in the proliferation of VSMCs [6][7][8]37].…”
Section: Discussionmentioning
confidence: 99%